Anyone, but not Everyone: Undergraduate Engineering Students' Claims of Who Can Do Engineering. Issue 2 (3rd May 2020) - Rohde, Jacqueline; Satterfield, Derrick J.; Rodriguez, Miguel; Godwin, Allison; Potvin, Geoff; Benson, Lisa; Kirn, Adam
Abstract : This paper examines students' claims about who can become an engineer and what it takes in engineering culture to be successful. Through longitudinal interviews with 20 undergraduate engineering students, we found that participants' descriptions of who can 'do' engineering were paradoxical. Participants simultaneously maintained that 'anyone' could do engineering and that individuals must also possess certain characteristics to become engineers. This study connects these students' responses to broader conversations regarding social advancement and meritocratic values within U.S. engineering culture. Participants' responses reflect a definition of engineering that may on the surface appear open but is in practice exclusionary to individuals who do not conform to certain expectations. While many discussions of culture in engineering focus on the values and practices of 'core' members such as faculty or practicing engineers, it is imperative to consider the understandings that students bring to their university and enact while being enculturated into the engineering profession. This study contributes to the literature by examining the ways cultural values are upheld and reified among undergraduate engineering students.